Comparison of Nd: YAG Laser Iridotomy Alone Versus Sequential Argon-Nd: YAG Laser Iridotomy in Patients with Primary Angle Closure Spectrum: Doi: 10.36351/pjo.v40i2.1765 - Khan, Paras; Khan, Rizwan; Attia Ahmad; Farah Huma; Fatima Zafar (Pakistan Journal of Ophthalmology, 2024)
Purpose: To compare the mean Nd: YAG energy used and mean decrease in IOP 3-hours post-laser, in Nd: YAG Laser iridotomyalone versus sequential Argon-Nd:YAGiridotomy in patients with primary angle closure spectrum. Study Design: Quasi experimental Study. Place and Duration of Study: Department of Ophthalmology, Allied Hospital, Faisalabad from March 2022 to August 2022. Methods: After taking approval from Ethical review board, 70 patients with angle closure spectrumwere included in the study. Out of 70, 25 patients were primary angle closure suspect (PACS), 28 had primary angle closure (PAC) and 17 patients had primary angle closure glaucoma (PACG). We sorted patients into Group A (those who underwent sequential Argon-Nd: YAG Laser peripheral iridotomy) and Group B (those who underwent Nd: YAG laser alone). Mean Nd: YAG energy used was noted in each group and compared using SPSS version 25.0. Mean decrease in IOP 3-hours post-laser was also noted and compared. Results: Mean decrease in IOP 3 hours post-laser was 5.46 ± 3.70 mmHg for sequential Argon-Nd: YAG LPI versus 3.46 ± 2.38 mmHg for Nd: YAG LPI alone (p-value = 0.009). Mean Nd: YAG energy used in sequential Argon-Nd: YAG LPI group was significantly lesser when compared to Nd: YAG LPI alone group (32.70 ± 38.87 versus 139.37 ± 62.32 mJ) which was found to be statistically significant (p = 0.0001). Conclusion: Sequential Argon-Nd-YAG laser iridotomy uses significantly less Nd:YAG energy than conventional Nd:YAG only method with better IOP control.